Penguatan Kapabilitas Peneliti Kebijakan Melalui Pelatihan Regulatory Impact Assesment di Kementerian Energi dan Sumber Daya Mineral - Maharani, Anita (Kreativasi : Journal of Community Empowerment, 2023)
The quality of policy formulation greatly influences the quality of services provided by ministries, in this case the Ministry of Industry which considers it necessary to provide opportunities to increase the capability of the State Civil Apparatus through Regulatory Impact Assessment (RIA) training. The purpose of this writing is to show the process of implementing one of the five materials presented in the RIA training series, namely the Introduction to RIA material, which was held at the initiative of one of the Institutions at the University of Indonesia in November 2022. The material presented to participants referred to a number of views. including from the OECD. The method of delivering material through the provision of material and exercises in class. To ensure there is a transfer of knowledge, before delivering the material a quiz is also carried out at the end of the material. The quiz scores shown by the participants increased when compared to before and after.